Economic evaluation of interventions for treatment-resistant depression: A systematic review - Hannah, Laura A.; Walsh, Cathy M.; Jopling, Louise; Perez, Jesus; Cardinal, Rudolf N.; Cameron, Rory A. (Frontiers in Psychiatry, 2023)
Background The extraordinarily high prevalence of treatment-resistant depression (TRD), coupled with its high economic burden to both healthcare systems and society, underscore how critical it is that resources are managed optimally to address the significant challenge it presents. Objective To review the literature on economic evaluation in TRD systematically, with the aim of informing future studies by identifying key challenges specific to the area, and highlighting good practices. Methods A systematic literature search across seven electronic databases was conducted to identify both within-trial and model-based economic evaluations in TRD. Quality of reporting and study design was assessed using the Consensus Health Economic Criteria (CHEC). A narrative synthesis was conducted. Results We identified 31 evaluations, including 11 conducted alongside a clinical trial and 20 model-based evaluations. There was considerable heterogeneity in the definition of treatment-resistant depression, although with a trend for more recent studies to use a definition of inadequate response to two or more antidepressive treatments. A broad range of interventions were considered, including non-pharmacological neuromodulation, pharmacological, psychological, and service-level interventions. Study quality as assessed by CHEC was generally high. Frequently poorly reported items related to discussion of ethical and distributional issues, and model validation. Most evaluations considered comparable core clinical outcomes – encompassing remission, response, and relapse. There was good agreement on the definitions and thresholds for these outcomes, and a relatively small pool of outcome measures were used. Resource criteria used to inform the estimation of direct costs, were reasonably uniform. Predominantly, however, there was a high level of heterogeneity in terms of evaluation design and sophistication, quality of evidence used (particularly health state utility data), time horizon, population considered, and cost perspective. Conclusion Economic evidence for interventions in TRD is underdeveloped, particularly so for service-level interventions. Where evidence does exist, it is hampered by inconsistency in study design, methodological quality, and availability of high quality long-term outcomes evidence. This review identifies a number of key considerations and challenges for the design of future economic evaluations. Recommendations for research and suggestions for good practice are made. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=259848&VersionID=1542096, identifier CRD42021259848.